2014
DOI: 10.1021/nl503558g
|View full text |Cite
|
Sign up to set email alerts
|

Direct Momentum-Resolved Observation of One-Dimensional Confinement of Externally Doped Electrons within a Single Subnanometer-Scale Wire

Abstract: Cutting-edge research in the band engineering of nanowires at the ultimate fine scale is related to the minimum scale of nanowire-based devices. The fundamental issue at the subnanometer scale is whether angle-resolved photoemission spectroscopy (ARPES) can be used to directly measure the momentum-resolved electronic structure of a single wire because of the difficulty associated with assembling single wire into an ordered array for such measurements. Here, we demonstrated that the one-dimensional (1D) confine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 44 publications
(134 reference statements)
6
47
1
Order By: Relevance
“…The former is assigned to the dimerization of the Au double row along the steps 22 . An ab-initio calculation confirmed that the dimerized double row Au chain in the middle of the terrace and a single honeycomb-like graphitic strip of Si atoms at the step edge is energetically most favorable 22 , which is consistent with STM 9,12,13,15,23,24 and XRD 20 studies. DFT calculations taking into account spin polarization led to the most recent structure model 6 referred to as original in the following.…”
supporting
confidence: 76%
“…The former is assigned to the dimerization of the Au double row along the steps 22 . An ab-initio calculation confirmed that the dimerized double row Au chain in the middle of the terrace and a single honeycomb-like graphitic strip of Si atoms at the step edge is energetically most favorable 22 , which is consistent with STM 9,12,13,15,23,24 and XRD 20 studies. DFT calculations taking into account spin polarization led to the most recent structure model 6 referred to as original in the following.…”
supporting
confidence: 76%
“…Recent studies on Si(hhk)-Au surfaces show that the gold-related bands are no longer free-electron-like, since they are strongly hybridized with the Si surface electronic states, particularly close to E F . [8][9][10][11] Hence, the nature of coupling between the wires and substrate defines the electronic properties of metallic chains.…”
Section: Introductionmentioning
confidence: 99%
“…According to angular resolved photoemission (ARPES) measurements [25,28,35], the Si(hhk)-Au systems are characterized by one or two-the number depends on the number of gold chains per terrace-parabolic electronic bands that cross the Fermi level. These bands are mostly located in the band gap of Si and make the systems metallic.…”
Section: Introductionmentioning
confidence: 99%